The Use of Digital Image Processing Applications by Radiology Students at Universitas Widya Husada Semarang - Lucky Restyanti Wahyu Utami; Masfufatun Jamil (Jurnal Ilmiah Wahana Pendidikan, 2026)
In the field of radiology, image processing is divided into 2, namely conventional image processing and digital image processing. Conventional image processing consists of manual image processing and automatic image processing. While digital image processing consists of computed radiography and digital radiography. This study aims to determine how the use of digital image processing applications using the RadiAnt DICOM viewer application in radiology students at Universitas Widya Husada Semarang after classroom learning activities. The type of research used is quantitative research. Respondents in this study were third-semester radiology students at Universitas Widya Husada Semarang in the 2024/2025 academic year. The results of the study obtained were an increase in knowledge about the RadiAnt DICOM viewer application with a percentage of 94.7%, an increase in the use of the RadiAnt DICOM viewer application with a percentage of 93% and the level of satisfaction with the RadiAnt DICOM viewer application hand on has a percentage of 63.2% after learning activities in third-semester radiology students at Universitas Widya Husada Semarang in the 2024/2025 academic year.